TiO2−Graphene Nanocomposites for Gas-Phase Photocatalytic Degradation of Volatile Aromatic Pollutant: Is TiO2−Graphene Truly Different from Other TiO2−Carbon Composite Materials? - Zhang, Yanhui; Tang, Zi-Rong; Fu, Xianzhi; Xu, Yi-Jun (ACS nano, 2010)
The nanocomposites of TiO2−graphene (TiO2−GR) have been prepared via a facile hydrothermal reaction of graphene oxide and TiO2 in an ethanol−water solvent. We show that such a TiO2−GR nanocomposite exhibits much higher photocatalytic activity and stability than bare TiO2 toward the gas-phase degradation of benzene, a volatile aromatic pollutant in air. By investigating the effect of different addition ratios of graphene on the photocatalytic activity of TiO2−GR systematically, we find that the higher weight ratio in TiO2−GR will decrease the photocatalytic activity. Analogous phenomenon is also observed for the liquid-phase degradation of dyes over TiO2−GR. In addition, the key features for TiO2−GR including enhancement of adsorptivity of pollutants, light absorption intensity, electron−hole pairs lifetime, and extended light absorption range have also been found in the composite of TiO2 and carbon nanotubes (TiO2−CNT). These strongly manifest that TiO2−GR is in essence the same as other TiO2−carbon (carbon nanotubes, fullerenes, and activated carbon) composite materials on enhancement of photocatalytic activity of TiO2, although graphene by itself has unique structural and electronic properties. Notably, this key fundamental question remains completely unaddressed in a recent report ( ACS Nano 2010, 4, 380 ) regarding liquid-phase degradation of dyes over the TiO2−GR photocatalyst. Thus, we propose that TiO2−GR cannot provide truly new insights into the fabrication of TiO2−carbon composite as high-performance photocatalysts. It is hoped that our work could avert the misleading message to the readership, hence offering a valuable source of reference on fabricating TiO2−carbon composites for their application as a photocatalyst in the environment cleanup.